Implementation of Dual Reciprocity Boundary Element Method to Solve The Mathematical Model of Steady Infiltration in Heterogeneous Soils Vertically - Paa, Armando Deminto; Solekhudin, Imam (IndoMS, 2025)
The Dual Reciprocity Boundary Element Method (DRBEM) is applied to Richards' equation for steady infiltration in unsaturated soil. The types of soil observed are Guelph Loam (GL) and Pima Clay Loam (PCL). A mathematical model for infiltration in heterogeneous unsaturated soil is built using Richards' equation and the Gardner model, with GL and PCL soil parameters. The heterogeneous soil types include GL-PCL and PCL-GL, where each soil is assumed to vary linearly in the vertical direction. This study investigates infiltration in vertically heterogeneous soils. Using DRBEM, the numerical simulation results of hydraulic conductivity are obtained as an approximation of the constructed mathematical model. Based on the numerical results of the hydraulic conductivity, the soil water potential values can be calculated using the Gardner model. The results of this study provide the distribution of the water content under steady-state conditions in heterogeneous soils, determined by hydraulic conductivity and soil water potential.